HUBUNGAN KEKUATAN OTOT TUNGKAI TERHADAP HASIL SEPAK SILA DALAM PERMAINAN SEPAK TAKRAW - Aplos Umpes; Agus Kurniadi; Muh Mawardi; La Robi; Emayanti Anggreni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the relationship between leg muscle strength and the results of the precept in the game of sepak takraw. Football is one of the dominant basic techniques used in receiving, controlling, and passing the ball, so its success is greatly influenced by the components of physical condition, especially the strength of the leg muscles. This study uses a quantitative approach with a correlational design to test the relationship between the variable of leg muscle strength as an independent variable and the result of the discipline as a bound variable. The research sample amounted to 30 high school sepak takraw athletes who were selected through purposive sampling techniques with the criteria of actively participating in training and not injured. The measurement of leg muscle strength was carried out using a leg dynamometer to obtain maximum strength data, while the ability of the precepts was measured through a 1-minute skill test by counting the number of legitimate ball touches. The data obtained was analyzed using the Product Moment (Pearson) correlation test at a significance level of 0.05 after meeting the assumptions of normality and linearity. The results of the analysis showed that there was a positive and significant relationship between leg muscle strength and the result of syllabus (r = 0.62; p < 0.05), which was in the category of strong relationship. These findings indicate that increasing leg muscle strength contributes to improving the ability of sepak sila techniques, so leg muscle strength development exercises need to be an important part of sepak takraw athlete coaching programs.v